PBL Model on Critical Thinking Skills and Learning Independence in Civics Education - Ni Made Ari Dwijayanti; I Wayan Lasmawan; I Nyoman Sudiana (Universitas Pendidikan Ganesha, 2026)
The limitation of interactive media in Civics learning, resulting in low levels of student engagement in the learning process. This study aimed to examine the effect of the Problem Based Learning (PBL) model based on interactive Wordwall media on the critical thinking skills and learning independence of fourth-grade students in Civic Education (PPKn) at elementary schools. This research employed a quasi-experimental method with a pretest-posttest control group design. The population of the study included all fourth-grade students in the Cluster III elementary schools in Selemadeg, and the sample was selected using purposive sampling. The research instruments consisted of a critical thinking skills test and a learning independence questionnaire, both of which had been tested for validity and reliability. Initial findings indicated that students’ critical thinking skills and learning independence were relatively low, which required a longer instructional period to achieve significant improvement. Following the implementation of the PBL model based on Wordwall, the results showed that: (1) students’ critical thinking skills significantly improved; (2) students’ learning independence also significantly increased; and (3) simultaneously, the PBL model based on Wordwall had a significant effect on both critical thinking skills and learning independence of fourth-grade students.